Diseño de un Plan de Desarrollo Turístico sostenible en la Comunidad de Peñas Blancas ubicada en la Parroquia Manuel Cornejo Astorga, Cantón Mejía Provincia de Pichincha. - Llerena Pilatuña, Verónica Alexandra (2018)
This project is about the "Design Sustainable Tourism Development plan” it is oriented by means of strategies tactics and policies to promote the tourism in the community of Peñas Blancas, Manuel Cornejo Astorga Parish, Pichincha Province. It used different methodologies as examples field research, problematic investigation, and by its nature in this investigation have been used different techniques like correlation, observation and bibliographic investigation. In addition, with instruments like MINTUR´s files 2017, questionnaire survey, they have determinate which are the results of investigation. Relative to determinate the actual situation in the place, it did an situational diagnostic in different aspects like social and cultural which result was the people suffers due to the education deficiency and health areas, in economical aspect the lack of job opportunities is its biggest limitation with respect to the environment aspect the community have many resources to efficiently and orderly to do tourism. By means of MINTUR´s files 2017, the information was taking account which results for the community and has five extractives, four hierarchy II and one hierarchy III, determining that for each attraction there are facilities that are carried out in an empirical way, for example, the houses of the villagers are adapted as lodging and food places, in addition it has adequate accessibility to the resources due to the second order routes that connect to each attraction. Finally, the proposal of strategies, tactics and policies was made through the strategic analysis matrix SWOT (strengths, opportunities, weaknesses, threats) which determined that the strengths have a weight of 1.83 against the weaknesses of 0.74, giving a total of 2.57 that is greater than the average of 2.50 according to the methodology of the EFI and EFE, which means that the internal strengths are favorable to direct the tourism, in the EFE the opportunities were weighted in 1.88 to the threats 1.01 giving a total of 2.87 which indicates that the external environment is favorable to the demands of tourism competitiveness, in addition it is posed 10 strategies, with their respective tactics and policies product of the results analyzed, which will allow the population to focus on the projects and activities that are required to be implemented so that tourism can be revitalized in the place.